Directive principles of state policy in the Indian constitution - Markandan, K. C. (Jalandhar, 1987)
An important aspect of the Constitution, which has not been adequately studied and hence, not properly appreciated, is the part relating to the 'Directive Principles of the State Policy.' Books on Constitution hardly devote more than a few pages to this aspect of the Constitution, which is to be regarded as fundamental in the governance of the State. The Directive Principles of State Policy in the Indian Constitution are the embodiment of the ideals and aspirations of the people of India and the goal towards which they expect the State to march for their attainment. The Directives elaborate, reinforce and ensure to the people of India what has been proclaimed in the Preamble, They are ideals, not in the sense that they are unattainable, but ideals of a welfare State, the realisation of which is dependent upon, primarily, finance and time factors. They are dynamic, as against fundamental rights which are static. Being so, they could neither be precisely worded nor could they be subjected to judicial purview and enforcement. It was thought essential to incorporate these ideals, within the body of the Constitution to impose, possibly, confidence in the minds of the people that what they had asked for, the State would strive after. If a chapter on Fundamental Rights is a must for a State of the modern democratic type with a written constitution, a chapter on Directive Principles of State Policy" is a 'must' for a Welfare State' with a written constitution.
Keywords: Constitutions-India